THE EFFECT OF SOIL WATER RETENTION CURVE HYSTERESIS ON THE STRENGTH OF UNSATURATED SOILS - SHWAN, BESTUN J. (Journal of Duhok University, 2017)
A modification of an existing soil water retention curve (SWRC) equation is presented in this paper which takes into consideration the effects of the soil capillarity (parameter a) and air entry value (so). The reformulated equation then was incorporated into the research version of the LimitState:GEO software to perform two parametric studies on the bearing capacity of a strip footing placed on the surface and total passive earth pressure for a frictional wall of 1 m height. The parametric analyses were to study the effect of SWRC hysteresis on the strength of unsaturated soils through parameter a and air entry value (so). The numerical bearing capacity and the passive earth pressure results were compared with the experimental data and the derived Rankine equations which take into account the effect of capillary rise, respectively. The numerical results showed that the effect of SWRC hysteresis has significant influence on the strength for both parametric studies.